Circulating ketone bodies and mortality in heart failure: a community cohort study - Oyetoro, Rebecca O.; Conners, Katherine M.; Joo, Jungnam; Turecamo, Sarah; Sampson, Maureen; Wolska, Anna; Remaley, Alan T.; Otvos, James D.; Connelly, Margery A.; Larson, Nicholas B.; Bielinski, Suzette J.; Hashemian, Maryam; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: The relationship between ketone bodies (KB) and mortality across the heart failure (HF) syndrome is not defined. Objectives: To assess the distribution of KB in HF, identify clinical correlates and examine associations between plasma KB and all-cause mortality in a population-based HF cohort. Methods: Plasma KB were measured by nuclear magnetic resonance spectroscopy. Multivariable linear regression was used to examine associations between clinical correlates and KB levels. Proportional hazard regression was used to examine associations between KB (modelled continuously and categorically) and mortality, with adjustment for several clinical covariates. Results: Among the 1,382 HF patients with KB measurements, the median (IQR) age was 78 (68, 84) and 52% were men. Median (IQR) KB was 180 (134, 308) μM. Higher KB levels were associated with advanced HF (NYHA class III-IV) and higher NT-proBNP (both P < 0.001). The median follow-up was 13.9 years, and 5-year mortality rate was 51.8% (95% CI: 49.1-54.4%). The risk of death increased when KB were higher (HRhigh vs. low group 1.23; 95% CI: 1.05-1.44), independently of a validated clinical risk score. The association between higher KB and mortality differed by ejection fraction (EF) and was noticeably stronger among patients with preserved EF. Conclusions: Most patients with HF had KB levels in line with those of healthy adults. KB were elevated in advanced HF. Higher KB levels were associated with a higher risk of death, particularly in patients with preserved EF.